2007
DOI: 10.1177/0883073807305788
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Statement for Standard of Care in Spinal Muscular Atrophy

Abstract: Spinal muscular atrophy is a neurodegenerative disease that requires multidisciplinary medical care. Recent progress in the understanding of molecular pathogenesis of spinal muscular atrophy and advances in medical technology have not been matched by similar developments in the care for spinal muscular atrophy patients. Variations in medical practice coupled with differences in family resources and values have resulted in variable clinical outcomes that are likely to compromise valid measure of treatment effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
804
0
97

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 786 publications
(910 citation statements)
references
References 111 publications
(118 reference statements)
9
804
0
97
Order By: Relevance
“…Accordingly, many SMA patients had nonmucocutaneous candidiasis, which usually only occurs in immunodeficient individuals 25. Moreover, pulmonary infection, especially pneumonia, appears to be a common feature of SMA patients 26, 27, 28, 29, 30. Decreased respiratory efficiency and stasis of secretions can increase risk of infections 29, 31.…”
Section: Potential Functional Consequences Of Lymphoid Organ Defectsmentioning
confidence: 99%
“…Accordingly, many SMA patients had nonmucocutaneous candidiasis, which usually only occurs in immunodeficient individuals 25. Moreover, pulmonary infection, especially pneumonia, appears to be a common feature of SMA patients 26, 27, 28, 29, 30. Decreased respiratory efficiency and stasis of secretions can increase risk of infections 29, 31.…”
Section: Potential Functional Consequences Of Lymphoid Organ Defectsmentioning
confidence: 99%
“…Although the diaphragm is spared in SMA, expiratory and intercostal muscles are weakened, making breathing difficult (D'Amico, 2011). This leads to recurrent chest infections, decreased respiratory function, impaired cough with poor secretion clearance, and eventually respiratory failure (Wang, 2007;D'Amico, 2011). …”
Section: Clinical Featuresmentioning
confidence: 99%
“…SMA should be on the list of differential diagnoses when a severely weak child or hypotonic baby presents with normal attentiveness and cognitive function (Menezes, 2011;D'Amico, 2011). SMA-related weakness is typically proximal and symmetrical, and tendon reflexes are diminished or absent (Wang, 2007;D'Amico, 2011). There are no associated sensory abnormalities (Wang, 2007).…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…15, 16 Natural history studies in the SMA type 1 population demonstrated shortened lifespan, with 68% mortality within the first 2 years of life 9, 10. With the advent of standardized care guidelines,17 the mortality of SMA type 1 infants has been reduced at 2 years of age to 30%, with nearly half of these infants dependent upon noninvasive ventilation 18. In a recent observational study, SMA infants who developed symptoms prior to 6 months of age demonstrated very poor motor function and significant motor loss electrophysiologically at the enrollment visit 19.…”
Section: Introductionmentioning
confidence: 99%